2011
DOI: 10.3855/jidc.1740
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four serological assays for the diagnosis of Chlamydia trachomatis in subfertile women

Abstract: Introduction: Chlamydia antibody testing (CAT) in serum has been introduced as a screening method in the infertility workup. We evaluated the test characteristics of two ELISA tests compared to micro-immunofluorescence tests (MIFs). MIFs are considered the gold standard in the C. trachomatis IgG antibodies detection. We also compared the accuracy of all CAT tests in predicting tubal subfertility, using laparoscopy as a reference. Methodology: Four commercial serological methods were used to analyse 101 serum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In contrast to our study, Muvunyi et al showed that peptide-based ELISA performed as well as two different IF assays (Muvunyi et al, 2012). However, the performance of the InoDiag tests presented here are consistent with previous studies that revealed good sensitivities and specificities of ELISA assays based on peptides from the MOMP (Muvunyi et al, 2012 ;Land JA et al, 2003).The new automated microarray from Inodiag® show similar performance than ELISA. It is well designed for small laboratories, since batches of only 2 to 4 samples can be tested with InoDiag.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to our study, Muvunyi et al showed that peptide-based ELISA performed as well as two different IF assays (Muvunyi et al, 2012). However, the performance of the InoDiag tests presented here are consistent with previous studies that revealed good sensitivities and specificities of ELISA assays based on peptides from the MOMP (Muvunyi et al, 2012 ;Land JA et al, 2003).The new automated microarray from Inodiag® show similar performance than ELISA. It is well designed for small laboratories, since batches of only 2 to 4 samples can be tested with InoDiag.…”
Section: Discussionsupporting
confidence: 87%
“…The sensitivity and specificity of Chlarnydia IgG antibody test (CAT) are comparable to that of HSG alone. In addition CAT is less cost prohibitive than PCR and has less risks than either HSG or laparoscopy [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7] It involves use of immunoglobulin G (IgG), A and M detections in either the serum or urine samples. Several studies have confirmed the reliability of using this simple serological test as a predictor of tubal blockage in different settings.…”
Section: Introductionmentioning
confidence: 99%